Enraizamento de estacas de gravioleira (Annona muricata L.) CV. "Gigante das Alagoas" - Santos, Maria Quiteria Cardoso dos (2010)
Soursop (Annona muricata L.) is a species of exotic flavor that has awaked the interest of the fruit market in the whole tropical world. Its vegetative propagation has been studied for some time, but so far, no one came across with a satisfactory technique for mass cloning elite trees. Stem cuttings is considered a quick and simple method of vegetative propagation for several wood plants and once established can be executed by anyone. This study aimed to set the main parameters for rooting cuttings of soursop and so establish a protocol for the commercial production of high quality clonal seedlings. Therefore, experiments of rooting cuttings were carried out in a green house of the CECA/UFAL in Rio Largo, Alagoas (S09° 27 ' 57 ", W34 ° 50 ' 1", 127m altitude). The cuttings used in this work were obtained from vigorous branches of soursop cv. Giant of Alagoas with 8-years-old trees. In a first experiment, it was studied the position of the cuttings in the branches and concentrations of AIB. Then, a second experiment was set to establish the best size and leaf area of the cuttings. Finally, a third experiment tested the best position to spraying auxins on the cuttings. The results obtained in the whole study showed that IBA 2000 and 4000 mg. kg-1) sprayed on leaves or stem base of the cuttings with 6 or 12 cm with a pair of halved leaves is appropriated to massive clonal propagation of soursop elite trees.